Implementation of Digital Entrepreneurship for Generation Z at Vocational School - Renita Setiyawan; Titik Ulfatun (Fakultas Tarbiyah Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study aims to describe the implementation of digital entrepreneurship and supporting and inhibiting factors for Generation Z at SMK Negeri 1 Purwodadi. This research uses a qualitative approach with a case study design-data collection techniques through observation, interviews, and documentation. Data was obtained from 10 11th-grade students in Accounting and Financial Institutions, Marketing, Culinary, and two entrepreneurship teachers. Data analysis techniques used are data collection, data reduction, data presentation, conclusions, and verification. The implementation of digital entrepreneurship at SMK Negeri 1 Purwodadi is structured through entrepreneurial learning and practice. Several supporting and inhibiting factors exist in implementing digital entrepreneurship at SMK Negeri 1 Purwodadi. Supporting factors include the implementation team, parental support, and awareness of the importance of digital technology. Meanwhile, inhibiting factors include students' need for more interest in digital entrepreneurship, limited internet access, and fear of failure.